Human Resources Management Practices and Total Quality Management (TQM) is the Precondition to Gain the Sustainable Competitive Advantage in the Bangladesh Ready-Made Garments Sector - Rashid, Farhana; Taib, Che Azlan; Yusoff, Rushami Zien; Ahmad, Mohd Akhir (Asian Institute of Research, 2020)
Bangladesh Garments manufacturing industry is expanding at a rate of 20% per year and around 76% of the export earnings are came from RMG sector (BEPB, 2018). Currently 4.2 million workers are working in this sector where 4490 manufacturing units are in operation (BGMEA, 2018). Bangladesh Ready-Made Garments (RMG) shows remarkable growth and significant contribution in the country's economic development though product and service qualities are yet a considerable problem to worry about. RMG companies in Bangladesh are not fully aware about the impacts and value of Total Quality Management (TQM) implementation. At the same time, Bangladesh garments industry fully labor intensive rather than technology oriented as Bangladesh is the cheapest labor country, the average labor cost per hour is only $0.3.Researchers argue that effective implementation of HRM and TQM practices is a main criteria and predictor of gaining sustainability in business. As, it is notable to mention that in case of Bangladesh RMG sector most of the existing literature give more emphasis and discuss about the infrastructural and strategic matters whereas TQM and Human Resource Management (HRM) practices in an attempt to improve sustainable competitive advantage is still a debate both theoretically as well as empirically. In this research tried to point out that HRM practices and TQM are positively related to organizational sustainable competitive advantage. In this aspect, literature's proved that, HR practices didn't get much attention which need to be measured and analysis in the aspect of Bangladesh RMG sectors quality performance improvement as in RMG sector human resources is the main advantage for industrial growth and sustainable competitive advantage in business. So this study is required to lift up this expectation to fulfill this research gap So there is a huge gap for further research. Proposed research direction and conclusion are discussed in conclusion of this research.